Biological Evaluation of Heterocycle Moiety of Some Novel azoles Derivatives as Antibacterial and Antifungal potential Agents - abozar roeintan (Fasa University of Medical Sciences, 2018)
Background & Objective: Azole nucleuses are very important part of antimicrobial, analgesic and anti-inflammatory drugs. The azole class of compounds is the most popular among the antibacterial and antifungal classes because of its lower toxicity, higher efficacy and a broad spectrum of activity. Today, Efforts have focused on the development of new, less toxic and more efficacious antifungal and antibacterial drugs, with the novel mechanism of action. In this study, we tried to investigate the antibacterial and antifungal effects of the new azole derivatives. Materials & methods: This research is a descriptive - cross sectional study. The antibacterial and antifungal activity of compounds was evaluated using the minimum inhibitory concentration (MIC) method on a series of gram positive and gram negative bacterial strains and Aspergillus niger, Aspergillus flavus, Candida albicans. The Minimum Inhibitory Concentration from the growth of this bacteria and fung ranges from 12.5 mg/ml to 200 mg/ml. Results: Among the tested compounds, 4- Nitro, 2- methyl imidazole hetrocycle-pathic compound exerted potent in vitro antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis and Staphylococcus aureus while compounds (imidazole, benzimidazole hetrocycle-pathic compound) exhibited potent in vitro antifungal activity against Candida albicans, Aspergillus flavus and Aspergillus niger. Conclusion: Our results indicated that the designed derivatives (4- Nitro, 2- methyl imidazole, imidazole and benzimidazole hetrocycle-pathic compounds) showed effective antibacterial and antifungal activity mainly against a series of gram positive and gram negative bacterial strains. On the other hand, the tested compounds had an appropriate spectrum effect, because they showed antibacterial effect on both positive and negative strains.